The Cordillera Blanca fault system as structural control of the Jurassic-Cretaceous basin in central-northern Peru - Romero Fernández, Darwin (2008)
Many works related to the Cordillera Blanca fault system exist (e.g. Bonnot, 1984; McNulty and Farber, 2002). These studies were mainly in the central part of the Cordillera Blanca fault, between northern Yungay and southern Recuay, without taking account the northern outcrops in the Pallasca zone and to the south the Cajatambo zone. The present study presents a new interpretation of the Cordillera Blanca fault system, based on stratigraphic and structural observations of the Jurassic-Cretaceous Chicama-Goyllarisquizga basin in centralnorthern Peru between Pallasca-Huaraz-Cajatambo, which form part the Cordillera Blanca fault system (CBFS).